La estructura del mercado mundial del poroto: Implicaciones para los paises de America Latina y la Republica Argentina - Pachico, Douglas H. (1982)
Important features of world legume trade are discussed, emphasizing bean. World production and trade during the 1960`s and 70`s are analyzed and the bean trade standards in major regions of the world are described. Bean markets in West European countries and import demand in Latin America, the Near East, and SubSaharan Africa are analyzed. Implications of the world situation of bean trade in Argentina are also discussed. The increase in demand for beans is slight in world markets. To compete for world markets bean production has to be highly efficient and costs should be minimized. A continued investment in market surveys is required. (CIAT)